Public Awareness of Healthy Lifestyle among Iraqi Population - Taher, Taqi Mohammed Jwad (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2023)
Background: A healthy lifestyle is a way of life that lowers the risk of being seriously ill or dying early. It includes making wise choices that can help people thrive as they move through their life's journey, like eating a healthy diet and being physically active. Objective: This study aims to assess public knowledge and awareness regarding healthy lifestyles. Methods: A cross-sectional study was conducted among 128 people relative to primary healthcare center visitors in Wasit province in Iraq. The data was collected using a self-administered questionnaire derived from a previously published article consisting of two parts. Results: In this study, around 66.4% of the sample knew about the food pyramid, and about 44.5% of them used it in their daily lives. The majority (60.6%) were eating three meals during the day, and only 44.6% skipped some meals during the day. Only one (0.8%) mentioned drinking alcohol, and 46.1% have a smoking habit. The majority (64.8%) of the sample never exercised for at least 30 minutes a day. A significant association was detected between gender and knowledge about the food pyramid (p=0.001), and a significant association was also found between smoking and the presence of chronic disease (p=0.029). Conclusion: It is important for the public to be aware of healthy lifestyles. Iraqi people still need to increase their knowledge and awareness by implementing health education.